Urban Battle Command in the 21st Century - Glenn, Russell W. (RAND Corporation, 2005)
In every operation, the functions of command, control, intelligence, surveillance, and reconnaissance (ISR), and communications are all fundamental to success. But in cities, the dense population, many manmade structures, and other challenges act to severely impede these functions in several ways. This monograph contemplates the nature of those challenges and proposes several recommendations to surmount them in both the short and longer terms.